Learning With a Project Aproach: an experience of a pedagogical support for supervision and teacher development - Leal da Costa, Conceição (2015)
In this chapter we will present and evaluate an in-service training program provided by the University of Évora department of Pedagogy and Education for pre-school and primary teachers involved in supervising student teachers in their practicum during the initial teacher education program – ―Learning through a Project Approach in pre-schooland primary school‖ (LPA). The methodology used is based on the concept of pedagogic isomorphism (Niza, 2009) structuring the course in a Project Approach (PA). Teachers started to identify their knowledge and also their needs and questions about the PA and they designed the course in collaboration, aiming to answer the questions they identified. All teachers were involved in bibliographic research about PA, they shared and discussed individual PA experiences and they carried out synthesis about the new knowledge and answers to the problems they identified that were than discussed in the group. The analysis of the teachers‘ voices expressed in the course assessments, demonstrate the way they designed and accomplished their projects of learning and provided evidence of the significance of this learning experience, which they were able to transfer to their practices like teachers and trainers